Facial rejuvenation using stem cell conditioned media combined with skin needling: A split‐face comparative study. (21st July 2020) - El‐Domyati, Moetaz; Moftah, Noha H.; Nasif, Ghada A.; Ameen, Sameh W.; Ibrahim, Michel R.; Ragaie, Maha H.
Abstract: Background: The use of stem cells derived growth factors is representing a novel treatment modality in facial rejuvenation. Nowadays, skin needling is considered a very famous treatment of skin aging. However, the addition of such derived products, augments its therapeutic efficacy in the management and delay of skin aging. Objective: Comparing the effect of amniotic fluid mesenchymal stem cell derived conditioned media (AF‐MSC‐CM) combined with skin needling versus the needling alone in the management of facial aging. Methods: Both sides of the face of ten volunteers, suffering from facial aging, were treated with five sessions of skin needling, 2 weeks apart. After skin microneedling, AF‐MSC‐CM was added topically to the right side only. Clinical, histological, and morphometrical assessment of the treated skin was done at 1 month after the last session. Results: The percentage of improvement of aged skin increased significantly on the combined treated side (AF‐MSC‐CM and dermaroller [DR]), when compared with the other side (DR only) ( P  < .001). Remodeling of the dermal structures was observed mainly on the combined side. Meanwhile, histometry of the epidermis revealed a significant increase in the epidermal thickness on both treated sides. Conclusion: AF‐MSC‐CM combined with skin needling was more efficient in managing facial aging than skin needling alone.